2018
DOI: 10.1159/000493121
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Long-Term Efficacy and Safety of Adalimumab in Patients with Ulcerative Colitis: Results from a 6-Year Real-World Clinical Practice

Abstract: Background: Although evidence for the short- to medium-term efficacy of adalimumab in ulcerative colitis (UC) patients is emerging, there are a limited number of reports on the long-term efficacy of adalimumab. This study was to understand baseline demographic features, which potentially could be risk factors for relapse or colectomy following induction of remission by adalimumab in UC patients. Additionally, factors affecting long-term outcomes were to be identified. Methods: Twenty-one patients with UC who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Two studies were included for the meta-analysis ( Figures 2 and 3 ). 57 , 58 The random-effects summary showed an annual LOR of 11.7% (95% CI, 5.5-25.1; I 2 = 82.1%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies were included for the meta-analysis ( Figures 2 and 3 ). 57 , 58 The random-effects summary showed an annual LOR of 11.7% (95% CI, 5.5-25.1; I 2 = 82.1%).…”
Section: Resultsmentioning
confidence: 99%
“… 12 , 23–39 , 49–52 , 56 , 57 , 59–66 , 69 , 70 Outcomes for ADA were described in 23 studies. 11 , 24 , 25 , 28 , 31 , 33 , 37 , 40–48 , 53–55 , 57 , 58 , 67 , 68 Forty-one were retrospective cohort studies, and 9 were prospective cohort studies. Characteristics of all included studies are provided in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that not only the decrease in CDAI score but also the decrease in CRP values is significant in terms of remission follow-up. 16 Sugimoto et al 17 in their study on UC patients, showed that CRP levels started to decrease and Hb increased in the fourth week of ADA treatment. In our study, in line with the literature, it was found that disease activation scores and CRP levels decreased and Hb values increased.…”
Section: Discussionmentioning
confidence: 97%